A Difficult Relationship : Declining (but Productive) FDI Inflows in Turkey - Kalemli-Ozcan, Sebnem; Sánchez-Martín, Miguel Eduardo; Thirion, Gilles (World Bank, Washington, DC, 2017)
This paper assesses two research questions: has the presence of foreign firms contributed to productivity increases in Turkey, and how could Turkey increase foreign direct investment inflows? First, the analysis applies dynamic regressions in differences over an AMADEUS firm-level data set. Similar to the results for other emerging countries, Turkish firms that received foreign direct investment will see an increase in productivity after the fourth year. The paper finds evidence of negative but small competition spillovers over domestic firms in the same sector of the multinational, as well as positive and large knowledge spillovers to domestic firms in broader two-digit sectors. This finding constitutes a case for foreign direct investment attraction policies in Turkey. Second, based on the findings of the cross-country regressions, the paper argues that Turkey could increase its attractiveness to foreign investors by strengthening institutional quality, in particular the rule of law, and mitigating exchange rate volatility.